NEW STUDENT ADMINISTRATION SYSTEM AT LPK GANESHA - Bambang Krismanto; Sahni Damerianta Purba, Skom, MM (Jurnal Sistem Informasi, 2002)
Based on the description above, the authors draw conclusions that are from thesechapters. The authors conclusions that can give is:1. Computerization as proposed pemecehan problems can help regarding the existingproblems in data processing where the volume from day to day data more and more.This will be felt more slowly when being done with the manual system.2. How to store the necessary data can be properly maintained for safety frompossible loss or omission and does not require a lot of space.